READINESS OF POSTGRADUATE STUDENTS TO MARRY (Descriptive Study toward Postgraduates Student at State the School of Postgraduate Programme State University of Padang) - Putriani, Lisa (Jurnal Konselor, 2015)
This study purpose to describe self readiness of graduate students to get married in terms of gender, cultural background, and economic conditions. The research method was ex post facto by using a factorial design 2 x 2 x 2. The population were graduate students class of 2013 and 2014 State University of Padang who was not married yet. The total sample were 300 people selected by random cluster sampling technique combined with purposive sampling technique. The instrument was a questionnaire. Data analyzed by analysis of variance (ANOVA). The result showed: the level of self readiness graduate students to get married in terms of gender, cultural background, and economic conditions were in high category.Â Keywords: Self Readiness for Married, Gender, Background Culture, Economic Conditions